The Evolving Landscape of Environmental, Social, and Governance (ESG)Practices and Their Impact on The Banking Industry: A Review with a Focus on Nepal - Luitel, Iswor (Adhyayan Journal, 2026)
The objective of this article is to explore the growing field of Environmental, Social, and Governance (ESG) practices worldwide, with a particular focus on their application within the Nepalese banking industry, detailing its evolution from Corporate Social Responsibility (CSR) and its critical role in assessing sustainability. This study is an attempt to investigate the effects of ESG on the profitability of Nepalese Bank. A narrative review methodology has been employed by selecting the articles from 2003-2026 in the study. It delves into the components of ESG, the obligation of disclosure, and the complex relationship between ESG performance and financial outcomes globally. This study focuses on the emerging stage of ESG adoption and current practices within the Nepalese banking industry, regulatory influences, and the challenges it has faced. The study found that Nepal’s banking industry, a cornerstone of its developing economy, is currently in the introductory stage of ESG adoption, primarily relying on voluntary CSR disclosures rather than mandatory ESG reporting. The discussion underscores the necessity of integrating ESG principles into core business strategies for sustainable growth and enhanced stakeholder trust, particularly in developing country like Nepal. Finally, it identifies gaps in current literature and proposes future research directions to further elucidate the dynamics of ESG in the financial sector.